Shift in the profile and prognostic implications in invasive fungal rhinosinusitis: experience of 10 years in a tertiary center - Raúl Mellidez-Acosta; Lidia Torres-García; Miguel Saro-Buendía; Natalia Jaramillo-Ángel; Javier Cabrera-Guijo; Catalina Bancalari-Díaz; Noelia Muñoz-Fernández; Lucas Fito-Martorell; Miguel Armengot-Carceller; Alfonso García-Piñero (The Egyptian Journal of Otolaryngology)
Abstract Background Despite appropriate treatment, mortality of acute invasive fungal rhinosinusitis remains exceedingly high, surpassing 50%. Evidence on how to optimize its management is still limited. We present a case series from our institution aiming to fill the knowledge gap. Methods A retrospective descriptive study was conducted, selecting cases treated at our institution between January 2012 and January 2022. The following variables were analyzed: gender, age, underlying conditions, symptoms, histological study outcomes, microbiological study outcomes, administered antifungal treatment, surgical interventions, and survival following diagnosis. Results Seventeen patients were included in our study. The mean age was 55 years, with 12 males and 5 females. The most frequents underlying conditions were hematological malignancies (76.5%) and solid organ transplantation (11.8%). Surgical interventions were performed on 15 patients (88%), with 6 patients (35.3%) requiring a second intervention and 2 patients (11.8%) undergoing at least 3 interventions.3% patients succumbed to causes directly related to rhinosinusitis, with an average survival of 22 days, and 52.9% patients subsequently passed away due to complications related to their underlying condition, with an average survival of 171 days. Mid-term overall mortality was 88.2%, with an average survival of 111 days. Conclusion A shift in the patient profile was observed. Less fulminant courses have been evidenced, being oncohematotological disease and solid organ transplantation the main predisposing conditions, instead of poorly controlled diabetes. Even if direct mortality rates from AIFR are reduced (around 35%), the overall mortality rate of these patients is close to 90% with a median survival of less than 6 months. Then, an intense focus on the underlying disease and related complications is essential.